Mengantisipasi Genangan Air Dengan Pemanfaatan Paralon Bekas Sebagai Biopori Pada Perumahan Subsidi di Kota Makassar (Studi Kasus: Perumahan Nasional Panakukkang) - Zulharnah, Zulharnah; Mastutie, Faizah; Yunus, Andi Ibrahim; Sompa, Andi (Penerbit Widina, Widina Media Utama, 2024)
The implementation of construction often causes several problems, one of which is waste resulting from the use of building materials in the form of pipes. Paralon are pipes made of plastic. Biopori infiltration holes are cylindrical holes made of paralon that are made vertically into the ground. Biopori aims to restore soil fertility, protect water systems and preserve the carrying capacity of the environment. The aim of this service activity is to improve the quality of the housing environment by improving sanitation by making biopore holes. The implementation method is carried out by demonstration for subsidized housing. Based on the results of the form of community service activities carried out for housing residents Perumahan Nasional Panakukkang, in the form of training activities on the use of used goods into handicrafts made from used plastic to improve the creative economy, this was carried out after delivering the counseling material followed by the practice of installing biopores around and in the housing yard. Based on the results of activities with housing residents, it can be concluded that the use of paralon is an environmentally friendly alternative to biopori made from polyvynil chloride as the main ingredient of biopori.ABSTRAKPelaksanaan pembangunan sering menimbulkan beberapa masalah, salah satunya limbah hasil penggunaan bahan bangunan berupa pipa. Paralon adalah pipa-pipa yang terbuat dari bahan plastik. Lubang resapan biopori adalah lubang silinder berbahan paralon yang dibuat secara vertikal ke dalam tanah. Biopori bertujuan memulihkan kesuburan tanah, melindungi tata air, dan kelestarian daya dukung lingkungan. Tujuan kegiatan pengabdian ini adalah untuk meningkatkan kualitas lingkungan perumahan melalui perbaikan sanitasi dengan membuat lubang biopori. Metode pelaksanaan dilakukan secara demonstrasi kepada perumahan bersubsidi. Berdasarkan hasil dari bentuk kegiatan pengabdian kepada masyarakat yang dilakukan kepada warga Perumahan Nasional Panakukkang, berupa kegiatan pelatihan pemanfaatan barang bekas menjadi kerajinan tangan yang berbahan dasar dari plastik bekas untuk meningkatkan ekonomi kreatif maka dengan dilakukannya setelah penyampaian materi penyuluhan diikuti dengan praktek pemasangan biopori disekitar dan halaman perumahan. Berdasarkan hasil kegiatan kepada warga perumahan dapat disimpulkan bahwa pemanfaatan paralon ini merupakan alternatif biopori ramah lingkungan yang terbuat dari polyvynil chloride sebagai bahan utama biopori.